Challenges of the Digital Age for Parents and Teachers in the Development of Personalities of Students of SMP Negeri 1 Sambi - Nita Safitri; Mutohharun Jinan (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Everyone worldwide, including students, has been affected by the rapid development of digital media due to advances in science, technology, and information. Everyone has a unique personality. However, in general, personalities can be divided into two categories: good and bad. The purpose of this study is to find out the challenges parents and teachers face in the digital era in developing the students’ personalities at SMP Negeri 1 Sambi. This research uses qualitative methods and uses intensive data processing techniques. The data used included observation, document study, questionnaires, and interviews. The results showed that parents and teachers of students face more complex challenges in building children's personalities in the current digital era, such as uncontrolled information, easily accessible information, and the influence of a strong digital environment. In addition, the use of digital media also has significant effects, including positive and negative effects on the life’s students of SMP Negeri 1 Sambi. Parents, teachers, and schools must play a role to minimize the negative effects of digital media on the development of students' personhood.